Functional morphology of the reproductive system of Galathea intermedia (Decapoda: Anomura) - Kronenberger, Katrin; Brandis, Dirk; Storch, Volker (Journal of morphology, 2004)
Spermatophore formation in Galathea intermedia begins in the proximal part of the vas deferens. The contents subsequently form a spermatophoric ribbon, the so-called “secondary spermatophore,” in its distal part. A strongly muscular ductus ejaculatorius is present in the coxa of the fifth pereiopod which builds up pressure for the extrusion of the spermatophoric ribbon. After extrusion, the ribbon is caught by the first gonopod, while the second gonopod dissolves the matrix of the ribbon. During copulation the spermatophores are randomly placed on the sternum of the female, near the genital opening, by the fifth pereiopods of the male. Subsequent ovulation of the female via the genital opening, an active process accomplished through muscular activity, results in fertilization of the eggs by the exploding spermatophores. External intersexes are characterized by both male and female external sexual characters, but in all individuals only male gonads are present. No trace of a female reproductive system could be detected. Thus, these external intersexes are exclusively functional males. J. Morphol. 262:500-516, 2004. © 2004 Wiley-Liss, Inc.